2022
DOI: 10.1017/s0021932022000256
|View full text |Cite
|
Sign up to set email alerts
|

Short birth interval and associated factors in rural India: A cross-sectional study

Abstract: Short Birth Interval (SBI) is one of the main causes of adverse maternal and child health outcomes. A 33-month birth-to-birth interval between two successive live births should be followed to minimize the risk of adverse maternal and child health. This study aimed to examine the prevalence of SBI and the associated factors in rural India. Information on 98,522 rural mothers from the fourth round of National Family Health Survey data was analyzed. Bivariate statistics, logistic regression, Moran’s I, and Cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
3
2
1
Order By: Relevance
“…Women between the ages of 25 and 34 years had a 31% higher prevalence of suboptimal birth interval than those aged 35 to 49 years, and the risk was increased by about two-fold for younger women (15–24 years). This finding is in agreement with the result of the previous studies that reported older maternal age as a protective factor for short birth spacing [ 12 , 13 , 15 , 16 , 23 , 34 ]. This might be attributed to the fact that younger women have inadequate reproductive knowledge [ 35 ] and limited participation in the decision regarding contraceptive use and therefore more likely to experience closely spaced births than older women [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Women between the ages of 25 and 34 years had a 31% higher prevalence of suboptimal birth interval than those aged 35 to 49 years, and the risk was increased by about two-fold for younger women (15–24 years). This finding is in agreement with the result of the previous studies that reported older maternal age as a protective factor for short birth spacing [ 12 , 13 , 15 , 16 , 23 , 34 ]. This might be attributed to the fact that younger women have inadequate reproductive knowledge [ 35 ] and limited participation in the decision regarding contraceptive use and therefore more likely to experience closely spaced births than older women [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis revealed that the overall prevalence of suboptimal birth spacing among women in SSA was 43.9% (43.7%-44.1%), with considerable within-country variations from 23.3% in South Africa to 59.3% in Chad. The level of suboptimal birth spacing practice observed in this study is higher than the prevalence reported from the studies conducted in Pakistan (23%) [ 12 ], Bangladesh (26%) [ 13 ], and rural India (50%) [ 16 ] but lower than the finding of systematic review in Ethiopia (47%) [ 14 ], the studies in ten high fertility African countries (59%) [ 17 ], and thirteen SSA countries (56%) [ 18 ]. Variations in the level of suboptimal birth spacing across the studies might be attributed to differences in the population characteristics, religious and sociocultural contexts, access to reproductive health services like contraception and other fertility-related services, and differences in healthcare infrastructure across the settings.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The ndings this study were found to be in line with the study conducted in Northwest Ethiopia (12). However, it was lower than the study conducted in Uganda(52.4%), Tanzania (48.4%), rural India (50%), Sub-Saharan Africa (58.7%), and other places of Ethiopia (62.9%) (2,(13)(14)(15)(16)). On the other hand, this nding is higher than studies conducted in Northern Ethiopia(23.3%,) and Bangladesh (26% ) respectively (4,17).…”
Section: Discussionsupporting
confidence: 83%
“…Most Indian studies have focused on predictors of birth interval with limited focus on the interval between marriage and first birth ( 13 15 ). Moreover, only a few studies conducted sufficient statistical analyses for time, i.e., survival analysis.…”
Section: Introductionmentioning
confidence: 99%